2014
DOI: 10.1002/2014gl060461
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between magnetosonic waves and radiation belt electrons: Comparisons of quasi‐linear calculations with test particle simulations

Abstract: Quasi-linear theory (QLT) has been commonly used to study the Landau resonant interaction between radiation belt electrons and magnetosonic (MS) waves. However, the long-parallel wavelengths of MS waves can exceed their narrow spatial confinement and cause a transit-time effect during interactions with electrons. We perform a careful investigation to validate the applicability of QLT to interactions between MS waves, which have a distribution in frequency and wave normal angle, and radiation belt electrons usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(126 citation statements)
references
References 32 publications
4
121
0
Order By: Relevance
“…With the ðÀ1Þ lÀ1 term missing, Bortnik's formulas produce an opposite behavior of perpendicular motion, while the corrected formulas produce a result that agrees well with full particle simulation using Lorentz solver. Using the corrected formulas, Li et al 30 recently showed that the test particle simulation of interactions between magnetosonic waves and energetic electrons is in good agreement with quasilinear theory when the waves propagate enough wavelengths along the ambient magnetic field lines.…”
Section: Comparison With Bell's Equation: Sign Problemmentioning
confidence: 91%
“…With the ðÀ1Þ lÀ1 term missing, Bortnik's formulas produce an opposite behavior of perpendicular motion, while the corrected formulas produce a result that agrees well with full particle simulation using Lorentz solver. Using the corrected formulas, Li et al 30 recently showed that the test particle simulation of interactions between magnetosonic waves and energetic electrons is in good agreement with quasilinear theory when the waves propagate enough wavelengths along the ambient magnetic field lines.…”
Section: Comparison With Bell's Equation: Sign Problemmentioning
confidence: 91%
“…For instance, the 8–9 October 2012 storm, the 17 March 2013 storm, and the 28–29 June 2013 storm, as denoted by the red vertical lines in Figure , occurred corresponding to the southward turning of IMF B z and the enhancement of solar wind dynamic pressure. The dynamic physics of radiation belt relativistic electrons during the first two storms, including chorus wave acceleration, ULF wave‐driven radial diffusion, scattering loss due to plasmaspheric hiss and EMIC waves, and the effects of plasmaspheric erosion/recovery and magnetopause shadowing, have been extensively studied [e.g., Reeves et al ., ; Thorne et al ., ; Shprits et al ., ; J. Li et al ., ; W. Li et al ., ; Tu et al ., ; Hudson et al ., ; Yu et al ., ; Gkioulidou et al ., ; Xiao et al ., ].…”
Section: Long‐term Poststorm Decay Of Ultrarelativistic Electron Fluxesmentioning
confidence: 99%
“…Natural electromagnetic emissions of equatorial noise [Russell et al, 1970;Gurnett, 1976] are receiving increased attention because of their possible importance for electron dynamics in the radiation belts [Horne et al, 2007;Li et al, 2014;Bortnik et al, 2015;Shprits, 2016;Walker et al, 2015a;Ma et al, 2016]. These emissions are composed of a complex system of many spectral lines with spacing ranging from a few hertz to a few tens of hertz, linked to ion cyclotron frequencies in local or distant sources [Gurnett, 1976;Santolík et al, 2002a;Ma et al, 2014].…”
Section: Introductionmentioning
confidence: 99%